Casas de sementes do Cariri Cearense - Alves, Jorge Henrique (2023)
Creole seeds are essencial for the preservation of agrobiodiversisty and are generally stored in individual seed banks or in institutions and collective farmers. Seed houses has an important role in the Brazilian semi-arid region, including the territory of Cariri, Ceará. Mapping and knowing the diversity of materials in the seed houses is necessary to understand the impacts and advantages of this social technology, as well as to define strategies to strengthen these spaces through the social organization linked to the development of public policy. The aim of this research is to map the creole seed houses in Cariri, Ceará, and analyze the diversity of materials kept in them. For this, the seed houses were registered and mapped throughout the Cariri region using georeferencing to produce maps through the spatial analysis tool QGIS 3.26. Based on visits, observations, and collection of information about the creation and management of seed houses, information was obtained regarding seed diversity. Thirteen active seed houses were identified in Cariri, most of them present in the central region, where organized agriculture communities are concentrated and there is support from partner institutions in the management and structuring of the seed houses. There was a great diversity of species stored, with beans, corn, fava beans, rice, sesame and pumpkin being the main species.